Preparation method and application of aperture-adjustable two-dimensional MXene-conducting polymer layered separation membrane
By adding conductive polymers to MXene materials and performing in-situ electrochemical polymerization, a two-dimensional MXene-conductive polymer layered separation membrane with adjustable pore size was prepared, which solved the problem of swelling of MXene materials in water environment and the problem of pore size control. Efficient molecular and ion selective separation and water flux regulation are achieved.
Patent Information
- Application Number
- CN202411326279.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-23
AI Technical Summary
MXene materials are prone to swelling in water environments, resulting in increased membrane spacing, reduced interception capacity, and difficult to achieve precise pore size control and construction at the nano or EM scale, limiting its application in selective separation of molecules and ions.
By mixing the two-dimensional MXene nanosheets with conductive polymer monomer solution, vacuum-assisted filtration and in-situ electrochemical polymerization, a two-dimensional MXene-conductive polymer layered separation membrane with adjustable pore size was prepared, and the electrochemical properties were regulated by regulating the The membrane pore size achieves selective separation.
Controllable adjustment of water flux and selective separation of monovalent salts, divalent salts and dye molecules are achieved, the mechanical stability and antioxidant capacity of the membrane are improved, the preparation process is simplified, and the preparation process is adapted to different separation needs.
Smart Images

Figure CN119186271A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of membrane separation, and in particular relates to a preparation method and application of a two-dimensional MXene-conductive polymer layered separation membrane with adjustable pore size. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] With the growth of population and the rapid development of industrial economy, water shortage and water pollution have become one of the most severe challenges faced by human society. Membrane separation technology is one of the most promising water treatment technologies in the 21st century. It has the advantages of high separation efficiency, low energy consumption, convenient operation, easy integration and scale, and easy combination with other technologies. It has been highly valued by countries around the world and has great development potential.
[0004] In recent years, the development of new nano-functional materials has provided an opportunity for the preparation of high-performance membranes. Among them, two-dimensional nanomaterials have received great attention in the field of membrane separation technology due to their unique physical and chemical properties, microstructures and pore size screening characteristics. By controlling the stacking mode and spacing between two-dimensional nanomaterial sheets, the construction and precise regulation of nanochannels between sheets can be achieved, which can make the membrane show water permeability significantly higher than that of traditional separation membranes, and also have nanometer or angstrom-level precise and rapid molecular and ion separation capabilities. Transition metal carbon / nitrogen compound (MXene) material is a new type of two-dimensional nanosheet material, composed of 5 atomic layers (Ti and C atomic layers are stacked alternately). It has excellent mechanical rigidity and toughness, hydrophilicity, conductivity, electrochemical capacitance characteristics, material compatibility and adjustable functions. It can be assembled into a two-dimensional separation membrane with uniform nanometer or angstrom-level channels, which has great potential in water treatment and desalination. However, due to its excellent water affinity, MXene is prone to swelling in an aqueous environment, resulting in an increase in the distance between membrane layers, thereby reducing the spatial confinement ability of the membrane layer and reducing its interception capacity. The distance between membrane layers can be stabilized by molecular cross-linking and heat treatment of MXene membranes, but it is still very difficult to achieve precise control and construction of membrane pores at the nanometer or angstrom scale. Moreover, the distance between membrane layers stabilized by cross-linking and heat treatment is also difficult to further adjust on demand to meet different separation requirements. This limits its application in the controllable and selective separation of molecules and ions (such as selective separation of specific ions, dye desalination, etc.). Summary of the invention
[0005] In order to solve the above problems, the present invention provides a method for preparing a two-dimensional MXene-conductive polymer layered separation membrane with adjustable pore size, and also provides an application method for electrochemically regulating the pore size of the membrane for selective separation of molecules and ions. The two-dimensional MXene-conductive polymer layered separation membrane is prepared by vacuum-assisted filtration of MXene and in-situ electrochemical polymerization of conductive polymers; the application method of electrochemically regulating the pore size of the membrane for selective separation of molecules and ions is to use the two-dimensional MXene-conductive polymer layered separation membrane as the working electrode, apply an external voltage, utilize the electrochemical properties of MXene and conductive polymers, and the electrical responsiveness of conductive polymer nanostructures to selectively separate monovalent salts, divalent salts, and dye molecules.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The first aspect of the present invention provides a method for preparing a two-dimensional MXene-conductive polymer layered separation membrane with adjustable pore size, comprising:
[0008] The dispersion of the two-dimensional MXene nanosheets and the conductive polymer monomer solution are mixed evenly in a volume ratio of 1:1-1.2, and the mixture is loaded on a support membrane substrate by vacuum assisted filtration and dried to obtain a two-dimensional MXene-conductive polymer monomer composite membrane;
[0009] The conductive polymer monomer solution is used as an electrolyte, the two-dimensional MXene-conductive polymer monomer composite film is used as a working electrode, and in-situ electrochemical polymerization is performed in a three-electrode system to obtain;
[0010] Wherein, the conductive polymer monomer solution contains an acid dopant.
[0011] The composite membrane of the present invention is prepared by compounding a conductive polymer into the interlayer of a two-dimensional MXene membrane by a method of vacuum-assisted filtration + in-situ electrochemical polymerization, and utilizes the good electrochemical properties of MXene and conductive polymers and the electrical responsiveness of the conductive polymer nanostructure to regulate the membrane pore size, thereby achieving controllable regulation of water flux and selective separation of monovalent salts, divalent salts, and dye molecules.
[0012] In some embodiments, the concentration of the dispersion of the two-dimensional MXene nanosheets is 0.05 to 0.5 mg mL -1 .
[0013] In some embodiments, the conductive polymer monomer is selected from one of polyaniline, polypyrrole, polythiophene and their respective derivatives;
[0014] In some embodiments, the concentration of the conductive polymer monomer solution is 0.2-2.0M.
[0015] In some embodiments, the acid dopant is selected from at least one of hydrochloric acid, sulfuric acid, perchloric acid, salicylic acid, citric acid, p-toluenesulfonic acid, dodecylbenzenesulfonic acid, polystyrenesulfonic acid, polyacrylic acid, polyethylenesulfonic acid, and polymethacrylic acid;
[0016] In some embodiments, the concentration of the acid dopant in the conductive polymer monomer solution is 0.5-2.0M.
[0017] In some embodiments, in the three-electrode system, the counter electrode is an electrode made of platinum, gold, titanium, stainless steel, glassy carbon or graphite, and the reference electrode is a saturated calomel electrode or a silver / silver chloride electrode.
[0018] In some embodiments, the specific conditions of the in-situ electrochemical polymerization are: the potential range of the cyclic voltammetry scan is -0.2 to 1.2 V, and the scan rate is 0.005 to 0.05 V s -1 , the number of scanning cycles is 10 to 100 times.
[0019] More specifically, they include:
[0020] (1) Ti3AlC2 is etched with a hydrochloric acid solution of LiF and then ultrasonically stripped, and the unstripped Ti3AlC2 precipitate is removed by centrifugation to obtain a dispersion of two-dimensional MXene nanosheets. A conductive polymer monomer solution is then prepared and added to the MXene dispersion. After sufficient mixing, it is loaded on a support membrane substrate by vacuum-assisted filtration and naturally dried at room temperature for 6 to 8 hours to form a two-dimensional MXene-conductive polymer monomer composite membrane.
[0021] (2) using a cyclic voltammetry in-situ electrochemical polymerization method to polymerize conductive polymer monomer molecules on the two-dimensional MXene-conductive polymer monomer composite membrane obtained in step (1), using a conductive polymer monomer solution as an electrolyte and a two-dimensional MXene-conductive polymer monomer composite membrane as a working electrode, performing an electrochemical cyclic voltammetry scan under a three-electrode system (working electrode, counter electrode and reference electrode), controlling the voltage range, scanning speed and number of scanning cycles of the cyclic voltammetry scan, and polymerizing the conductive polymer monomer in the MXene interlayer pores in situ through electrochemistry. After the polymerization reaction is completed, the prepared membrane is rinsed with high-purity water and then treated at 30 to 60° C. for 1 to 2 hours to obtain a two-dimensional MXene-conductive polymer layered separation membrane.
[0022] The second aspect of the present invention provides a two-dimensional MXene-conductive polymer layered separation membrane with adjustable pore size prepared by the above method.
[0023] In some embodiments, the thickness of the two-dimensional MXene-conductive polymer layered separation membrane is 50 to 1000 nm.
[0024] The third aspect of the present invention provides a method for electrochemically regulating membrane pore size for selective separation of molecules and ions, comprising:
[0025] The above-mentioned two-dimensional MXene-conductive polymer layered separation membrane is sealed into a membrane assembly, wherein the two-dimensional MXene-conductive polymer layered separation membrane serves as a separation membrane and a conductive electrode at the same time, is connected to a DC power supply through a wire, and a counter electrode is placed on the water inlet side or the permeate outlet side. By applying a voltage between the membrane electrode and the counter electrode, an electric potential is generated on the membrane surface, driving counter ions (ions with an electrical charge opposite to that of the membrane layer) in the conductive polymer between the membrane layers to regulate the membrane pore size by ion embedding or ion de-embedding, thereby achieving controllable regulation of water flux and selective separation of monovalent salts, divalent salts, and dye molecules.
[0026] In some embodiments, the counter electrode is one of a platinum mesh, a gold mesh, a titanium mesh, a stainless steel mesh, and a carbon fiber cloth.
[0027] In some embodiments, the voltage between the two-dimensional MXene-conductive polymer layered separation membrane electrode and the counter electrode ranges from 0 to 3.0 V, and the membrane surface potential ranges from 0 to -1.5 V vs. Ag / AgCl.
[0028] The present invention relates to a preparation method and application method of a two-dimensional MXene-conductive polymer layered separation membrane with adjustable pore size, which has the following characteristics: the preparation method of the two-dimensional MXene-conductive polymer layered separation membrane is to embed a conductive polymer monomer into the interlayer of a two-dimensional MXene membrane obtained by vacuum-assisted filtration, and then prepare it through in-situ electrochemical polymerization. In the prepared two-dimensional MXene-conductive polymer layered separation membrane, the conductive polymer is located between the MXene membrane layers and forms a MXene-conductive polymer composite structure through cross-linking polymerization, which has good conductivity. In addition, the conductive polymer structure also has electrochemical responsiveness, and the embedding and de-embedding of ions under electrochemistry can change its volume, thereby causing a change in the membrane interlayer spacing (for example, when a negative potential is applied to the membrane, as the negative potential increases, the ion embedding increases, the volume of the conductive polymer increases, and the membrane interlayer spacing becomes larger). Therefore, the two-dimensional MXene-conductive polymer layered separation membrane can control the membrane pore size through electrochemical regulation, thereby realizing controllable regulation of water flux and selective separation of molecules and ions.
[0029] Beneficial Effects of the Invention
[0030] (1) In the present invention, the preparation of the two-dimensional MXene-conductive polymer layered separation membrane with adjustable pore size is simple and easy to operate, and does not require expensive equipment; the presence of the conductive polymer in the two-dimensional MXene-conductive polymer layered separation membrane layer greatly improves the mechanical stability and antioxidant capacity of the membrane structure, and has excellent conductive properties and electrochemical characteristics; the membrane can be used as a separation membrane and a conductive electrode at the same time, and an electric potential is applied to the membrane layer. By electrochemically regulating the membrane pore size, the water flux can be controlled and regulated, and the selective separation of monovalent salts, divalent salts, and dye molecules can be achieved.
[0031] (2) The preparation method of the present invention is simple, practical and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.
[0033] Figure 1 This is a cyclic voltammetry scanning curve image of a two-dimensional MXene-polyaniline layered separation membrane (Example 1) prepared using the preparation method involved in the present invention.
[0034] Figure 2 This is a scanning electron microscope image of the surface of a two-dimensional MXene-polypyrrole layered separation membrane (Example 2) prepared using the preparation method involved in the present invention.
[0035] Figure 3 This is a scanning electron microscope image of the cross section of a two-dimensional MXene-polypyrrole layered separation membrane (Example 2) prepared by the preparation method of the present invention. 1 is a two-dimensional MXene-polypyrrole layered separation membrane layer, and 2 is a polyethersulfone support membrane substrate. DETAILED DESCRIPTION
[0036] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0037] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0038] Embodiment 1:
[0039] A method for preparing a two-dimensional MXene-conductive polymer layered separation membrane with adjustable pore size is specifically implemented according to the following steps:
[0040] (1) 1.6 g LiF was added to 20 mL 9 mol L-1 Ti3AlC2 was etched in HCl solution at 45 °C for 36 h, and then ultrasonically stripped. The unstripped Ti3AlC2 precipitate was removed by centrifugation to obtain a dispersion of two-dimensional MXene nanosheets, which was diluted to 0.05 mg mL -1 ; Then, a 0.2 M aniline monomer solution was prepared, which contained 1.0 M p-toluenesulfonic acid. Subsequently, 10 mL of MXene dispersion was evenly mixed with 10 mL of aniline monomer solution. It was then loaded on a polyvinylidene fluoride hollow fiber membrane substrate by vacuum-assisted filtration and naturally dried at room temperature for 8 hours to form a two-dimensional MXene-aniline composite membrane.
[0041] (2) polymerizing aniline monomer molecules on the two-dimensional MXene-aniline composite film obtained in step (1) by a cyclic voltammetry in-situ electrochemical polymerization method, using the aniline monomer solution as the electrolyte and the two-dimensional MXene-aniline composite film as the working electrode, performing electrochemical cyclic voltammetry scanning under a three-electrode system (membrane electrode, platinum counter electrode and silver / silver chloride reference electrode), controlling the voltage range of the cyclic voltammetry scanning to be 0-1.2 V, and the scanning speed to be 0.01 V s -1 The scanning cycle number was 10 times. Aniline monomer was polymerized in situ in the pores between MXene layers by electrochemical in situ. After the polymerization reaction, the prepared membrane was rinsed with high-purity water and then treated at 30°C for 2h to obtain a two-dimensional MXene-polyaniline layered separation membrane.
[0042] An application method of electrochemically regulating membrane pore size for selective separation of molecules and ions, the specific implementation steps are:
[0043] The above-mentioned two-dimensional MXene-polyaniline layered separation membrane was sealed into a membrane assembly, wherein the two-dimensional MXene-polyaniline layered separation membrane served as both a separation membrane and a conductive electrode, and was connected to a DC power supply via a platinum wire. A platinum mesh was placed on the water inlet side as a counter electrode, and the two-dimensional MXene-polyaniline layered separation membrane was used as a cathode and a voltage was applied. 2 g L -1 The NaCl solution was used as the raw water to test the water permeability and salt retention rate of the membrane. When the applied voltage was 0V, 0.5V, 1.0V, 1.5V, 2.0V, and 2.5V (the corresponding membrane surface potential was 0V vs.Ag / AgCl, -0.14V vs.Ag / AgCl, -0.38V vs.Ag / AgCl, -0.63V vs.Ag / AgCl, -0.91V vs.Ag / AgCl, and -1.19V vs.Ag / AgCl), the permeability was 16.2L m -1 h -1 bar -1 、17.2L m -1 h-1 bar -1 、19.4L m -1 h -1 bar -1 、22.7L m -1 h -1 bar -1 、25.3L m -1 h -1 bar -1 、26.5L m -1 h - 1 bar -1 The salt retention rates were 27.0%, 17.6%, 2.5%, 0.9%, 0.3% and 0.2% respectively.
[0044] Embodiment 2:
[0045] A method for preparing a two-dimensional MXene-conductive polymer layered separation membrane with adjustable pore size is specifically implemented according to the following steps:
[0046] (1) 1.6 g LiF was added to 20 mL 9 mol L -1 Ti3AlC2 was etched in HCl solution at 40 °C for 48 h, and then ultrasonically stripped. The unstripped Ti3AlC2 precipitate was removed by centrifugation to obtain a dispersion of two-dimensional MXene nanosheets, which was diluted to 0.2 mg mL -1 ; Then prepare a 1.0M pyrrole monomer solution and add hydrochloric acid to make its concentration 1.0M. Then, evenly mix 10mL of MXene dispersion with 10mL of pyrrole monomer solution, load it on the polyethersulfone flat membrane substrate by vacuum assisted filtration, and dry it naturally at room temperature for 6h to form a two-dimensional MXene-pyrrole composite membrane.
[0047] (2) polymerizing pyrrole monomer molecules on the two-dimensional MXene-pyrrole composite film obtained in step (1) by a cyclic voltammetric in-situ electrochemical polymerization method, using the pyrrole monomer solution as the electrolyte and the two-dimensional MXene-pyrrole composite film as the working electrode, performing electrochemical cyclic voltammetric scanning under a three-electrode system (membrane electrode, titanium sheet counter electrode and saturated calomel reference electrode), controlling the voltage range of the cyclic voltammetric scanning to be -0.1 to 1.0 V, and the scanning speed to be 0.05 V s -1 The scanning cycle number was 50 times. Pyrrole monomer was polymerized in situ in the pores between MXene layers by electrochemical in situ. After the polymerization reaction, the prepared membrane was rinsed with high-purity water and then treated at 40°C for 1h to obtain a two-dimensional MXene-polypyrrole layered separation membrane.
[0048] An application method of electrochemically regulating membrane pore size for selective separation of molecules and ions, the specific implementation steps are:
[0049] The above-mentioned two-dimensional MXene-polypyrrole layered separation membrane was sealed into a membrane assembly, wherein the two-dimensional MXene-polypyrrole layered separation membrane served as both a separation membrane and a conductive electrode, and was connected to a DC power supply via a titanium wire. A titanium mesh was placed on the water inlet side as a counter electrode, and the two-dimensional MXene-polypyrrole layered separation membrane was used as a cathode and a voltage was applied. 2 g L -1 The Na2SO4 solution was used as the raw water to test the water permeability and salt retention rate of the membrane. When the applied voltage was 0V, 0.5V, 1.0V, 1.5V, 2.0V, and 2.5V (the corresponding membrane surface potential was 0V vs.Ag / AgCl, -0.14V vs.Ag / AgCl, -0.38V vs.Ag / AgCl, -0.63V vs.Ag / AgCl, -0.91V vs.Ag / AgCl, and -1.19V vs.Ag / AgCl), the permeability was 1.33L m -1 h -1 bar -1 、13.8L m -1 h -1 bar -1 、14.9L m -1 h -1 bar -1 、17.1L m -1 h -1 bar -1 、19.0L m -1 h -1 bar -1 、21.5L m -1 h - 1 bar -1 The salt retention rates were 90.2%, 87.4%, 86.2%, 84.8%, 38.3% and 0.5% respectively.
[0050] Embodiment 3:
[0051] A method for preparing a two-dimensional MXene-conductive polymer layered separation membrane with adjustable pore size is specifically implemented according to the following steps:
[0052] (1) 1.6 g LiF was added to 20 mL 9 mol L -1 Ti3AlC2 was etched in HCl solution at 50 °C for 24 h, and then ultrasonically stripped. The unstripped Ti3AlC2 precipitate was removed by centrifugation to obtain a dispersion of two-dimensional MXene nanosheets, which was diluted to 0.5 mg mL-1 ; Then, a 1.0 M 3,4-ethylenedioxythiophene monomer solution was prepared, which contained a 1.0 M concentration of polystyrene sulfonic acid. Subsequently, 5 mL of the MXene dispersion was evenly mixed with 5 mL of the pyrrole monomer solution. The solution was then loaded onto a polysulfone flat membrane substrate by vacuum-assisted filtration and naturally dried at room temperature for 8 h to form a two-dimensional MXene-3,4-ethylenedioxythiophene composite membrane.
[0053] (2) polymerizing 3,4-ethylenedioxythiophene monomer molecules on the two-dimensional MXene-3,4-ethylenedioxythiophene composite film obtained in step (1) by a cyclic voltammetric in-situ electrochemical polymerization method, using the 3,4-ethylenedioxythiophene monomer solution as an electrolyte and the two-dimensional MXene-3,4-ethylenedioxythiophene composite film as a working electrode, performing electrochemical cyclic voltammetric scanning under a three-electrode system (membrane electrode, graphite sheet counter electrode and saturated calomel reference electrode), controlling the voltage range of the cyclic voltammetric scanning to be -0.2 to 1.0 V, and the scanning speed to be 0.5 V s -1 The scanning cycle number was 100 times. 3,4-ethylenedioxythiophene monomer was polymerized in situ in the pores between MXene layers by electrochemical in situ. After the polymerization reaction, the prepared membrane was rinsed with high-purity water and then treated at 60°C for 1h to obtain a two-dimensional MXene-poly 3,4-ethylenedioxythiophene layered separation membrane.
[0054] An application method of electrochemically regulating membrane pore size for selective separation of molecules and ions, the specific implementation steps are:
[0055] The above-mentioned two-dimensional MXene-poly (3,4-ethylenedioxythiophene) layered separation membrane was sealed into a membrane assembly, wherein the two-dimensional MXene-poly (3,4-ethylenedioxythiophene) layered separation membrane was used as a separation membrane and a conductive electrode at the same time, and was connected to a DC power supply through a stainless steel wire. A carbon fiber cloth was placed on the permeate outlet side as a counter electrode, and the two-dimensional MXene-poly (3,4-ethylenedioxythiophene) layered separation membrane was used as a cathode and a voltage was applied. 2 g L -1 NaCl and 0.1 g L -1The mixed solution of Congo red dye is raw water. When the applied voltage is 0V, 0.5V, 1.0V, 1.5V, 2.0V, and 2.5V (the corresponding membrane surface potential is 0V vs.Ag / AgCl, -0.14V vs.Ag / AgCl, -0.38V vs.Ag / AgCl, -0.63V vs.Ag / AgCl, -0.91V vs.Ag / AgCl, -1.19V vs.Ag / AgCl), the dye retention rates are 98.9%, 99.0%, 99.1%, 99.5%, 99.6%, and 99.8%, respectively, and the NaCl salt retention rates are 28.0%, 19.9%, 4.7%, 1.0%, 0.5%, and 0.2%, respectively.
[0056] Comparative Example 1
[0057] The difference from Example 1 is that only MXene is used for vacuum-assisted filtration to prepare a two-dimensional MXene layered separation membrane, which is used as a working electrode for separation application. Specific steps for implementation:
[0058] 1.6 g LiF was added to 20 mL 9 mol L -1 Ti3AlC2 was etched in HCl solution at 45 °C for 36 h, and then ultrasonically stripped. The unstripped Ti3AlC2 precipitate was removed by centrifugation to obtain a dispersion of two-dimensional MXene nanosheets, which was diluted to 0.05 mg mL -1 Then, 10 mL of MXene dispersion was loaded on the polyvinylidene fluoride hollow fiber membrane substrate by vacuum-assisted filtration and dried naturally at room temperature for 8 h to form a two-dimensional MXene layered separation membrane.
[0059] The above-mentioned two-dimensional MXene layered separation membrane was sealed into a membrane assembly, wherein the two-dimensional MXene layered separation membrane served as both a separation membrane and a conductive electrode, and was connected to a DC power supply via a platinum wire. A platinum mesh was placed on the water inlet side as a counter electrode, and a voltage was applied using the two-dimensional MXene layered separation membrane as a cathode. 2 g L -1 The NaCl solution was used as the raw water to test the water permeability and salt retention rate of the membrane. When the applied voltage was 0V, 0.5V, 1.0V, 1.5V, 2.0V, and 2.5V (the corresponding membrane surface potential was 0V vs.Ag / AgCl, -0.14V vs.Ag / AgCl, -0.38V vs.Ag / AgCl, -0.63V vs.Ag / AgCl, -0.91V vs.Ag / AgCl, and -1.19V vs.Ag / AgCl), the permeability was 3.5L m -1 h -1 bar -1 、3.4L m-1 h -1 bar -1 、3.6Lm -1 h -1 bar -1 、3.6L m -1 h -1 bar -1 、3.7L m -1 h -1 bar -1 、3.8L m -1 h -1 bar -1 The salt retention rates were 15.2%, 15.4%, 15.1%, 14.7%, 14.8% and 14.5% respectively.
[0060] Comparative Example 2
[0061] The difference from Example 1 is that no electrochemical polymerization is performed, and the two-dimensional MXene-aniline composite membrane prepared in step (1) is directly used as the working electrode for separation application. Specific steps are as follows:
[0062] 1.6 g LiF was added to 20 mL 9 mol L -1 Ti3AlC2 was etched in HCl solution at 45 °C for 36 h, and then ultrasonically stripped. The unstripped Ti3AlC2 precipitate was removed by centrifugation to obtain a dispersion of two-dimensional MXene nanosheets, which was diluted to 0.05 mg mL -1 ; Then, a 0.2 M aniline monomer solution was prepared, which contained 1.0 M p-toluenesulfonic acid. Subsequently, 10 mL of MXene dispersion was evenly mixed with 10 mL of aniline monomer solution. It was then loaded on a polyvinylidene fluoride hollow fiber membrane substrate by vacuum-assisted filtration and naturally dried at room temperature for 8 hours to form a two-dimensional MXene-aniline composite membrane.
[0063] The above-mentioned two-dimensional MXene-aniline composite membrane was sealed into a membrane assembly, wherein the two-dimensional MXene-aniline composite membrane served as both a separation membrane and a conductive electrode, and was connected to a DC power supply via a platinum wire. A platinum mesh was placed on the water inlet side as a counter electrode, and the two-dimensional MXene-aniline composite membrane was used as a cathode and a voltage was applied. 2 g L -1The NaCl solution was used as the raw water to test the water permeability and salt retention rate of the membrane. When the applied voltage was 0V, 0.5V, 1.0V, 1.5V, 2.0V, and 2.5V (the corresponding membrane surface potential was 0V vs.Ag / AgCl, -0.14V vs.Ag / AgCl, -0.38V vs.Ag / AgCl, -0.63V vs.Ag / AgCl, -0.91V vs.Ag / AgCl, and -1.19V vs.Ag / AgCl), the permeability was 11.8L m -1 h -1 bar -1 、11.9L m -1 h -1 bar -1 、11.9L m -1 h -1 bar -1 、12.0L m -1 h -1 bar -1 、12.1L m -1 h -1 bar -1 、12.1L m -1 h -1 bar -1 The salt retention rates were 23.1%, 22.5%, 22.6%, 22.3%, 22.4% and 22.2% respectively.
[0064] Comparative Example 3
[0065] The composite film was prepared by the method of Example 1 in patent CN 115268119 A. The test results showed that the prepared composite film could not achieve the regulation of the pore size between MXene layers, and did not have the ability to selectively separate molecules and ions.
[0066] From the comparison between Example 1 and Comparative Examples 1 and 2, it can be seen that compared with the two-dimensional MXene layered separation membrane or the two-dimensional MXene-aniline composite membrane "without electrochemical polymerization", the two-dimensional MXene-conductive polymer layered separation membrane of the present invention can achieve the regulation of the pore size between the MXene layers and has a better ability to selectively separate molecules and ions.
[0067] From the comparison between Example 1 and Comparative Example 3, it can be seen that in the present invention, the conductive polymer monomer is mixed with the MXene solution and vacuum filtered to allow the conductive polymer monomer to enter the interlayer of the MXene nanosheet, and then in situ electrochemical polymerization is performed; while in patent CN 115268119 A, the conductive polymer solution is directly used for electrodeposition and loaded on the surface of the MXene film. This method directly uses a conductive polymer and does not involve an electrochemical polymerization process, and cannot achieve the regulation of the pore size between the MXene layers, nor does it have the ability to selectively separate molecules and ions.
[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a two-dimensional MXene-conductive polymer layered separation membrane with adjustable pore size, characterized in that: include: The dispersion of the two-dimensional MXene nanosheets and the conductive polymer monomer solution are mixed evenly in a volume ratio of 1:1-1.2, and the mixture is loaded on a support membrane substrate by vacuum assisted filtration and dried to obtain a two-dimensional MXene-conductive polymer monomer composite membrane; The conductive polymer monomer solution is used as an electrolyte, the two-dimensional MXene-conductive polymer monomer composite film is used as a working electrode, and in-situ electrochemical polymerization is performed in a three-electrode system to obtain; Wherein, the conductive polymer monomer solution contains an acid dopant.
2. The method for preparing a two-dimensional MXene-conductive polymer layered separation membrane with adjustable pore size according to claim 1, characterized in that: The concentration of the dispersion of the two-dimensional MXene nanosheets is 0.05-0.5 mg mL -1 .
3. The method for preparing a two-dimensional MXene-conductive polymer layered separation membrane with adjustable pore size according to claim 1, characterized in that: The conductive polymer monomer is selected from one of polyaniline, polypyrrole, polythiophene and their respective derivatives; Alternatively, the concentration of the conductive polymer monomer solution is 0.2-2.0M.
4. The method for preparing a two-dimensional MXene-conductive polymer layered separation membrane with adjustable pore size according to claim 1, characterized in that: The acid dopant is selected from at least one of hydrochloric acid, sulfuric acid, perchloric acid, salicylic acid, citric acid, p-toluenesulfonic acid, dodecylbenzenesulfonic acid, polystyrenesulfonic acid, polyacrylic acid, polyethylenesulfonic acid, and polymethacrylic acid; Alternatively, in the conductive polymer monomer solution, the concentration of the acid dopant is 0.5-2.0M.
5. The method for preparing a two-dimensional MXene-conductive polymer layered separation membrane with adjustable pore size according to claim 1, characterized in that: In the three-electrode system, the counter electrode is an electrode made of platinum, gold, titanium, stainless steel, glassy carbon or graphite, and the reference electrode is a saturated calomel electrode or a silver / silver chloride electrode.
6. The method for preparing a two-dimensional MXene-conductive polymer layered separation membrane with adjustable pore size according to claim 1, characterized in that: The specific conditions of the in-situ electrochemical polymerization are: the potential range of the cyclic voltammetry scan is -0.2 to 1.2 V, and the scan rate is 0.005 to 0.05 V s -1 , the number of scanning cycles is 10 to 100 times.
7. A two-dimensional MXene-conductive polymer layered separation membrane with adjustable pore size prepared by the method according to any one of claims 1 to 6, characterized in that: The thickness of the two-dimensional MXene-conductive polymer layered separation membrane is 50 to 1000 nm.
8. A method for electrochemically regulating membrane pore size for selective separation of molecules and ions, characterized in that: include: The two-dimensional MXene-conductive polymer layered separation membrane described in claim 7 is sealed into a membrane component, wherein the two-dimensional MXene-conductive polymer layered separation membrane serves as a separation membrane and a conductive electrode at the same time, is connected to a DC power supply through a wire, and a counter electrode is placed on the water inlet side or the permeate outlet side. By applying a voltage between the membrane electrode and the counter electrode, an electric potential is generated on the membrane surface, and counter ions are driven to regulate the membrane pore size in the conductive polymer between the membrane layers by ion embedding or ion de-embedding, thereby realizing controllable regulation of water flux and selective separation of monovalent salts, divalent salts, and dye molecules.
9. The method for selectively separating molecules and ions by electrochemically regulating membrane pore size according to claim 8, characterized in that: The counter electrode is one of a platinum mesh, a gold mesh, a titanium mesh, a stainless steel mesh and a carbon fiber cloth.
10. The method for selectively separating molecules and ions by electrochemically regulating membrane pore size according to claim 8, characterized in that: The voltage between the two-dimensional MXene-conductive polymer layered separation membrane electrode and the counter electrode ranges from 0 to 3.0 V, and the membrane surface potential ranges from 0 to -1.5 V vs. Ag / AgCl.
Citation Information
Patent Citations
Heterojunction composite electrode based on CPs / 2D material and preparation method and application thereof
CN115268119A
MXene / conductive polymer composite aerogel and preparation method thereof
CN108530889A
Preparation method and application of conductive polymer / carbon nanotube composite nanofiltration membrane
CN109603566A
MXene / polyaniline composite membrane for water treatment, and preparation method thereof
CN110559880A
MXene-based composite filter membrane, preparation method thereof and application of MXene-based composite filter membrane in water treatment
CN113600025A